STUDENTS' RESPONSES TO JUDY BLUME'S IGGIE'S HOUSE - Andreas Kriswanto, - (2012)
The present study investigates the responses of college students to Judy Blume's Iggie's House. The study is carried out within the frameworks of Rossenblatt's reader response strategy. The data was taken by means of survey and questionnaire adapted from National Literacy Trust. The survey involves 10 students of English Department of Indonesia University of Education. The data was classified and identified based on Wall's (1996) response categories. The study shows that in responding, students could retell the story indicating that they generally could comprehend the story. The respondents were classified into 2 major groups which are group with positive attitude towards reading and group with negative attitude towards reading. As expected, in terms of criticizing and coherence level, respondents in the first group showed better responses than the second group. Interestingly, in spite of having supportive circumstances for reading, the majority of the respondents have a negative attitude towards reading. Several reasons contributing to these results are demanding environments, limited reading materials, pragmatic reading culture and so forth. This study can be treated as an input to help all concerned parties improve their awareness of reading, to assist future studies concerning reader response and reading interest.